PENGARUH BEBAN KERJA, KEPUASAN KERJA, DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PT. ABC - Yunita Maria Aurora Butar Butar (2022)
This study uses quantitative research which aims to determine and prove the effect of Workload, Job Satisfaction, and Work Environment on Employee Turnover Intention of PT. ABC. The sample technique used is the entire population as a sample of 64 employees. Data collection was carried out through distributing questionnaires. The data analysis technique used is the Partial Least Square (PLS) method. The test results obtained in this study are (1) workload has a positive and significant effect on turnover intention, (2) job satisfaction has a negative and significant effect on turnover intention, (3) work environment has a positive and significant effect on turnover intention. The implications of this research include theoretical and practical, that is, helping readers and researchers to understand and understand the influence of workload, job satisfaction, and work environment on employee turnover intention at work. This research is aimed at adding information to companies regarding employees' perceptions of workload, job satisfaction, work environment and turnover intention so that turnover is expected to decrease.